2005
DOI: 10.1590/s1678-77572005000200011
|View full text |Cite
|
Sign up to set email alerts
|

Surface tension of calcium hydroxide associated with different substances

Abstract: The purpose of this study was to evaluate the surface tension of calcium hydroxide (CH) associated with different substances (deionized distilled water, camphorated paramonochlorophenol, 2% chlorhexidine digluconate, Otosporin, 3% sodium lauryl ether sulphate; Furacin, PMC Furacin) using tensiometer. The action of the substances studied on the dentinal structure enhances the property of surface tension. This method consists in the application of force to separate a platinum ring immersed in the substances. Thu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
5
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 9 publications
3
5
0
Order By: Relevance
“…At pH 12, the contact angle and  values for NaOCl decreased to 52.1⁰ and 74.10.5 mN/m whereas slight changes were noted in the contact angle and  values for NaOH at pH 12, 41.6⁰ and 72.60.5 mN/m respectively. The results of our study agree with the results ofEstrela et al (2005) andBeattie et al (2014) who obtained 75.0 mN/m for NaOCl and 72.8 mN/m for NaOH, at pH of 12 respectively.…”
supporting
confidence: 93%
See 1 more Smart Citation
“…At pH 12, the contact angle and  values for NaOCl decreased to 52.1⁰ and 74.10.5 mN/m whereas slight changes were noted in the contact angle and  values for NaOH at pH 12, 41.6⁰ and 72.60.5 mN/m respectively. The results of our study agree with the results ofEstrela et al (2005) andBeattie et al (2014) who obtained 75.0 mN/m for NaOCl and 72.8 mN/m for NaOH, at pH of 12 respectively.…”
supporting
confidence: 93%
“…The  value for pure water was 70.80.5 mN/m at 35 °C. In the current literature, the mean values for water surface tension at 25 °C range from 70.0 mN/m to 72.7 mN/m(Beattie et al, 2014;Estrela et al, 2005) agreeing with the value obtained in this study. It can be clearly seen that the addition of NaOCl and/or NaOH increased the  value of water (refer toTable 7.2).…”
supporting
confidence: 92%
“…There is a great deal of disparity among the use of an optimum medium for Ca(OH) 2 that would aid in diminishing postoperative pain. According to Estrela et al, when calcium hydroxide distilled water (aqueous vehicle) paste was used, the liberation of Ca 2+ and OH - ions was faster and more significant, indicating their rapid action in reducing pain [ 19 38 ]. Another study by Gomes et al found that oily vehicles boost the antibacterial properties of Ca(OH) 2 against E. faecalis and other microorganisms, showing greater zones of microbial inhibition with oily vehicles than those with aqueous and viscous vehicles [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…Solubility was assessed by means of the method described by Estrela et al, 15 following #57 ADA specification. Cements were mixed and compacted into ring molds, producing round specimens, 20 mm in diameter and 1.5 mm thick.…”
Section: Solubility Testmentioning
confidence: 99%